A pastoral theology of immigration: Parish ministry at the intersection of Bible and newspaper. Issue 3 (22nd September 2021) - Zorn, Henry
Abstract: For Christians, the Bible is a source of truth that guides believers in daily life. Migration is a subject that is in the news almost daily. A Lutheran (ELCA) parish pastor offers his pastoral theology through insights and personal experience in navigating the intersection of the Bible and the newspaper. While the subject of migration is sensitive and hyper‐politicized, the gospel is a source of hope and provides a road map for blessed ministry with immigrants.